Strategi Peningkatan Usaha Tani Padi Sawah Untuk Meningkatkan Perekonomian Masyarakat Desa - Abdurrozzaq Hasibuan; Suhela Putri Nasution; Fitri Amja Yani; Henni Adlini Hasibuan; Nyak Firzah (Yayasan Literasi Sains Indonesia, 2022)
Rural agricultural development is an inseparable unit. Agriculture is the main component that sustains rural life. However, the role of the agricultural sector as a whole has not developed so that it has not succeeded in raising the position of farmers to the level of prosperity as expected. The role of the agricultural sector is faced with problems in line with the development of the rural economy. A strategy for developing the agricultural sector in the future is needed, through various conducive policy agendas, so that the role of the agricultural sector in the rural and national economy can be increased. The approach used in this study is a literature review approach. In collecting data, the authors collect data and information related to the strategy of increasing lowland rice farming in order to produce high and good rice production in order to improve the economy of rural communities through supporting data sourced from national and international journals. This literature study has the aim of formulating strategic priorities in the development of lowland rice farming that affect economic improvement in Indonesian villages including increasing the availability of quality rice and increasing the availability of quality seeds, increasing rice planting index, increasing farmers' income, and increasing the competence of farmers who The strategy formulation is more or less formulated through SWOT analysis, the QSP (Quantitative Strategic Planning) Matrix which combines the IFE (Internal Factor Evaluation), EFE (External Factor Evaluation), and the SWOT (Strengths, Weaknesses, Opportunities, Threats) matrix that has been obtained.